ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MENGGUNAKAN ALAT PELINDUNG DIRI - Kartika Dyah Sertiya Putri (The Indonesian Journal of Occupational Safety and Health, 2017)
Using personal protective equipment (PPE) is the last risk control to protect the workers from occupational safety and health hazards. Applying safety culture through obedience behavior of wearing PPE is important to do as the responsibility of the company to protect its workers from occupational safety and health hazards. The purpose of this research was to analyze factors which have correlation with obedience of wearing PPE in aluminum sulfate unit production PT. Liku Telaga Gresik.This research was analytical observational with a cross sectional design. Subject of this research was total population that consist of 114 workers. Data would be shown in a frequency distribution and cross tabulation afterwards analyzed using statistic chi square.The result of research showed that most of workers obeyed to wear PPE in workplace. Statistic analytical results showed that education (p=0.005; r=0.336) and attitude to the policy (p=0.045; r=0.233) are factors which has correlated with obedience of wearing PPE. Age (p=1), time of work (p=1), knowledge (p=0.483), motivation (p=1), personality (p=0.464), training (p=0.559), communication (p=0.72) and availability of PPE (p=0.652) have no correlation with obedience of wearing PPE.Keywords: behavior of wearing PPE,safety culture, workers in aluminum sulfate unit production